Perovskite-based nanocrystals : synthesis and applications beyond solar cells - Wang, Ning (2020)
The recent progress in perovskite nanocrystals, including synthetic methods and their applications beyond solar cells, is discussed. Specifically, different synthetic routes to prepare various perovskite nanocrystals are considered, followed by their applications, including light‐emitting diodes, amplified spontaneous emission and lasing, photodetectors, resistance random access memory devices, and piezoelectric nanogenerators. Finally, an outlook for the future potential applications and possible challenges of perovskite nanocrystals is addressed.